Normothermic ex vivo Heart Perfusion Combined With Melatonin Enhances Myocardial Protection in Rat Donation After Circulatory Death Hearts via Inhibiting NLRP3 Inflammasome-Mediated Pyroptosis - Lu, Jun; Xu, Liwei; Zeng, Zifeng; Xue, Chuqing; Li, Jiale; Chen, Xiong; Zhou, Pengyu; Lin, Shaoyan; Liao, Yuhui; Du, Xianjin; Yang, Ronghua; Zheng, Shaoyi (Frontiers in Cell and Developmental Biology, 2021)
Objective: The adoption of hearts from donation after circulatory death (DCD) is a promising approach for the shortage of suitable organs in heart transplantation. However, DCD hearts suffer from serious ischemia/reperfusion injury (IRI). Recent studies demonstrate that nucleotide-binding oligomerization domain-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome-mediated pyroptosis is a novel target to ameliorate myocardial IRI. Melatonin is shown to inhibit NLRP3 inflammasome-mediated pyroptosis. Therefore, this study is designed to verify the hypothesis that melatonin can protect the heart graft preserved with ex vivo heart perfusion (EVHP) against myocardial IRI via inhibiting NLRP3 inflammasome-mediated pyroptosis in a rat model of DCD. Methods: Donor-heart rats were randomly divided into 3 groups: 1) Control group: Non-DCD hearts were harvested from heart-beating rats and immediately preserved with allogenic blood-based perfusate at constant flow for 105 minutes in the normothermic EVHP system. 2) DCD-vehicle group and 3) DCD-melatonin group: Rats were subjected to the DCD procedure with 25 minutes of warm ischemia injury and preserved by the normothermic EVHP system for 105 minutes. Melatonin (200 μmol/L) or vehicle was perfused in the cardioplegia and throughout the whole EVHP period. Cardiac functional assessment was performed every 30 minutes during EVHP. The level of oxidative stress, inflammatory response, apoptosis, and NLRP3 inflammasome-mediated pyroptosis of heart grafts submitted to EVHP were evaluated. Results: 25-minute warm ischemia injury resulted in a significant decrease in the developed pressure, dP/dtmax, and dP/dtmin of left ventricular of the DCD hearts, while the treatment with melatonin significantly increased the developed pressure, dP/dtmax of the left ventricular of DCD hearts compared with DCD-Vehicle group. Furthermore, warm ischemia injury led to a significant increase in the level of oxidative stress, inflammatory response, apoptosis, and NLRP3 inflammasome-mediated pyroptosis in the hearts preserved with EVHP. However, melatonin added in the cardioplegia and throughout the EVHP period significantly attenuated the level of oxidative stress, inflammatory response, apoptosis, and NLRP3 inflammasome-mediated pyroptosis compared with DCD-Vehicle group. Conclusions: EVHP combined with melatonin post-conditioning attenuates myocardial IRI in DCD hearts by inhibiting NLRP3 inflammasome-mediated pyroptosis, which might expand the donor pool by the adoption of transplantable DCD hearts.